TECHNICAL CONSIDERATIONS FOR THE PLANNING OF ROOF GARDENS - Nizamettin KOÇ; Gül GÜNEŞ (Pamukkale University Journal of Engineering Sciences, 1998)
Increases in population, buildings, traffic density and air pollution is the most specific characteristics of metropol cities. These conditions effect the living quality negatively. That is why architectures and planners should find both aesthetic and functional planning approach in urban areas. Roof gardens, which affect positively urban ecology in many ways, have an important place in this approach. Planning aproach of roof gardens are rather different compare to ground level design. Structural elements under the roof gardens againist the infiltration of water. That is why it is important that roof garden plannings should have some layers shuclh as drainage, insulation, waterproofing, filter layers and irrigation andf drainage systems.